The Effectiveness Of Website/Webblog-Based Mosque Management Information Systems In Providing Accountable Information In Pekalongan City - Agus Arwani; Muhammad Masrur; Nasrul Khakim (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2018)
A mosque organization plays a role as a public sector organization that manages the mosque’s resources and activities. The management and resources in the mosque are mostly done voluntarily. The development of information technology (IT) has provided various means for management in managing business and decision-making. Nonetheless, the measurement or assessment of the quality of an effective information system is hard to carry out directly, including cost-benefit measurement. A descriptive quantitative approach was employed in this field research. The findings reveal the quality system, quality information, process quality, collaborative quality and service quality contributed to the mosque management information systems. Website/webblog-based mosque run effectively and obtained accountable information in the city of Pekalongan. The management of the mosque’s website in this city has been established effectively since it applies the management of mosque information systems by using DeLone and McLean’s model of information system success, which includes system quality management, collaborative quality, and service quality of website/webblog-based mosque in Pekalongan City.